ACCURACY OF SATELLITE OPTICAL OBSERVATIONS AND PRECISE ORBIT DETERMINATION - Shakun, L.; Koshkin, N.; Korobeynikova, E.; Strakhova, S.; Dragomiretsky, V.; Ryabov, A.; Melikyants, S.; Golubovskaya, T.; Terpan, S. (Одеські астрономічні публікації, 2017)
The  monitoring  of  low-orbit  space  objects (LEO-objects) is performed in the Astronomical Observatory  of  Odessa  I.I. Mechnikov  National  University (Ukraine) for many years. Decades-long arсhives of these observations  are  accessible  within  Ukrainian  network  of optical observers (UMOS). In this  work,  we  give an example  of  orbit  determination  for  the  satellite  with  the 1500-km height of orbit based on angular observations in our  observatory (Int.  No.  086).  For  estimation  of  the measurement accuracy and accuracy of determination and propagation of satellite position, we analyze the observations  of  Ajisai  satellite  with  the  well-determined  orbit. This  allows  making  justified  conclusions  not  only  about random errors of separate measurements, but also to analyze the presence of systematic errors, including external ones to the measurement process. We have shown that the accuracy of one measurement has the standard deviation about  1  arcsec  across  the  track  and  1.4  arcsec  along  the track and systematical shifts in measurements of one track do not exceed 0.45 arcsec. Ajisai position in the interval of  the  orbit  fitting  is  predicted  with  accuracy  better  than 30 m along the orbit and better than 10 m across the orbit for any its point.